Method for producing positive electrode for lithium secondary battery and positive electrode
The method of multi-stage rolling with controlled thickness change rates addresses the challenge of achieving high-density positive electrodes for lithium secondary batteries using lithium iron phosphate, ensuring adhesion and reducing defects, while also improving battery capacity and resistance.
Patent Information
- Application Number
- JP2023563242
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-12-24
- Filing Date
- 2022-12-23
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2042-12-23
AI Technical Summary
The challenge in manufacturing a positive electrode for lithium secondary batteries using lithium iron phosphate is achieving high density while preventing the active material layer from detaching from the current collector, which is exacerbated by the non-spherical shape of lithium iron phosphate and differences in mechanical properties between the active material and the current collector.
A method involving multiple rolling stages of the positive electrode slurry composition containing lithium iron phosphate and a binder, with specific thickness change rate controls during initial and subsequent rolling steps to ensure adhesion and achieve high density without layer detachment.
This method effectively suppresses the detachment of the positive electrode active material layer, allowing for the production of high-density electrodes with improved adhesion and reduced electrode defect rates, while also minimizing the binder content to lower battery resistance and enhance capacity.
Smart Images

Figure 0007674050000003 
Figure 0007674050000004 
Figure 0007674050000005
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority to Korean Patent Application No. 10-2021-0187036, filed on December 24, 2021.
[0002] The present invention relates to a method for manufacturing a positive electrode for a lithium secondary battery and the positive electrode, and more particularly to a method for manufacturing a positive electrode for a lithium secondary battery by multiple rolling and the positive electrode manufactured by such a method. [Background technology]
[0003] As technological development and demand for electric vehicles and energy storage systems (ESS) increases, the demand for batteries as energy sources is rapidly increasing, and various researches are being conducted on batteries that can meet various demands. In particular, researches on lithium secondary batteries, which have high energy density as a power source for such devices and have excellent life and cycle characteristics, are being actively conducted.
[0004] Lithium cobalt oxide (LCO), lithium nickel cobalt manganese oxide (LNCMO), lithium iron phosphate (LFP), etc. are used as positive electrode active materials for lithium secondary batteries.
[0005] Lithium iron phosphate is low-cost because it contains iron, which is a resource-abundant and low-cost material. In addition, the toxicity of lithium iron phosphate is low, so that environmental pollution can be reduced when lithium iron phosphate is used. In addition, since lithium iron phosphate has an olivine structure, the active material structure can be stably maintained at high temperatures compared to lithium transition metal oxides with a layered structure. This can improve the high-temperature stability and high-temperature life characteristics of the battery.
[0006] However, since lithium iron phosphate has a shape that is not spherical, the tap density of lithium iron phosphate is low, and it is difficult to manufacture a high-density positive electrode. To solve this problem, a high rolling ratio is required in the process of rolling the positive electrode slurry composition onto the positive electrode current collector. However, when the positive electrode slurry composition is rolled at a high rolling ratio, there is a problem in that the positive electrode active material layer is detached from the positive electrode current collector due to the difference in mechanical properties (e.g., elongation ratio, Poisson's ratio, etc.) between the positive electrode current collector and the positive electrode active material layer.
[0007] Therefore, in the past, in order to obtain a high-density positive electrode while preventing the detachment of the positive electrode active material layer, the content of the binder in the positive electrode slurry composition has been increased. However, when the content of the binder in the positive electrode slurry composition is increased, problems occur in that the resistance of the lithium secondary battery increases and the content of the positive electrode active material decreases relatively, resulting in a decrease in the battery capacity of the positive electrode.
[0008] As a result, in the manufacture of positive electrodes containing lithium iron phosphate, there is a demand for technological development for manufacturing high-density positive electrodes while preventing detachment of the positive electrode active material layer. Summary of the Invention [Problem to be solved by the invention]
[0009] The present invention has an object to provide a method for producing a positive electrode for a lithium secondary battery containing lithium iron phosphate, which produces a high-density positive electrode while preventing detachment of a positive electrode active material layer from a positive electrode current collector. [Means for solving the problem]
[0010] According to one embodiment of the present invention, there is provided a method for manufacturing a positive electrode for a lithium secondary battery, the method including: (S1) applying a positive electrode slurry composition containing lithium iron phosphate and a binder onto a current collector and drying the composition; and (S2) performing multi-stage rolling on the dried positive electrode slurry composition N times (N is an integer of 2 or more) to form a positive electrode active material layer, wherein in the rolling step, a thickness change rate of the positive electrode active material layer according to the following formula 1 is in the range of 5% to 15% during a first rolling step, and a thickness change rate of the positive electrode active material layer according to the following formula 1 is 3.5% or less during rolling steps after the first rolling step. Also provided is a positive electrode manufactured according to the method.
[0011] [Formula 1] Thickness change rate (%) = {thickness of the positive electrode active material layer rolled (K-1) times - thickness of the positive electrode active material layer rolled K times} x 100 / thickness of the positive electrode active material layer before rolling
[0012] In the above formula 1, K is an integer of 1 or more and N or less.
[0013] In one embodiment of the present invention, the rolling step may be performed in a multi-stage rolling process of 3 to 6 times.
[0014] In an embodiment of the present invention, after the rolling step, the positive electrode active material layer may have a porosity of 28% to 36%.
[0015] In an embodiment of the present invention, the positive electrode active material layer may have a thickness of 85 μm to 95 μm after the rolling step.
[0016] In an embodiment of the present invention, after the rolling step, the rolling ratio of the positive electrode active material layer may be 20% to 26%.
[0017] In one embodiment of the present invention, the dried positive electrode slurry composition may have a porosity of 55% or less.
[0018] In an embodiment of the present invention, after the first rolling, the rolling ratio of the positive electrode active material layer may be 10% or more.
[0019] In one embodiment of the present invention, the rolling step may be performed by a roll press method.
[0020] In one embodiment of the present invention, the lithium iron phosphate may be a compound represented by the following Chemical Formula 1:
[0021] [Chemical formula 1] Li 1+a Fe 1-x M x (PO 4-b )X b
[0022] In the above Chemical Formula 1, M includes any one or more elements selected from the group consisting of Al, Mg, Ni, Co, Mn, Ti, Ga, Cu, V, Nb, Zr, Ce, In, Zn, and Y, X includes any one or more elements selected from the group consisting of F, S, and N, and a, b, and x are -0.5≦a≦0.5, 0≦b≦0.1, and 0≦x≦0.5, respectively.
[0023] In one embodiment of the present invention, the lithium iron phosphate can be LiFePO4 with an olivine crystal structure.
[0024] In one embodiment of the present invention, the lithium iron phosphate may be included in the solid content of the positive electrode slurry composition in an amount of 94.90% by weight to 97.96% by weight.
[0025] The binder may be included in the positive electrode slurry composition in an amount of 0.5% by weight to 3.5% by weight of the solid content. Effect of the Invention
[0026] According to the present invention, when a positive electrode slurry containing lithium iron phosphate is rolled multiple times, the thickness change rate of the positive electrode active material layer is 3.5% or less when the positive electrode slurry is rolled after the first rolling, so that the detachment of the positive electrode active material layer from the positive electrode current collector is effectively suppressed, and as a result, it is possible to manufacture a high-density positive electrode with a significantly reduced electrode defect rate.
[0027] In addition, by using the above method, even if the binder content in the positive electrode slurry composition is at a low level, a high-density positive electrode having improved adhesion between the positive electrode current collector and the positive electrode active material layer (hereinafter, positive electrode adhesion) can be manufactured. In addition, the low binder content in the positive electrode active material layer can reduce the resistance of the lithium secondary battery, and the positive electrode active material content in the positive electrode active material layer can be relatively increased, improving the battery capacity of the positive electrode. [Brief description of the drawings]
[0028] [Figure 1] 1 is a photograph of the positive electrode produced in Example 1. [Diagram 2] 1 is a photograph of a positive electrode produced in Comparative Example 1. [Diagram 3] 1 is a photograph of a positive electrode produced in Comparative Example 2. [Figure 4] 1 is a photograph of a positive electrode produced in Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] The advantages and features of the present invention, and the methods for achieving them, will become clear from the following detailed description of the embodiments in conjunction with the accompanying drawings. However, the present invention is not limited to the embodiments disclosed below, and may be embodied in various different forms, and the embodiments are provided only to make the disclosure of the present invention complete and to fully convey the scope of the invention to those skilled in the art to which the present invention pertains, and the present invention is defined only by the claims. The same reference numerals refer to the same elements throughout the specification.
[0030] Unless otherwise defined, all terms (including technical and scientific terms) used herein may be used as meanings commonly understood by those having ordinary skill in the art to which the present invention belongs. Furthermore, terms defined in commonly used dictionaries are not to be interpreted ideally or excessively unless clearly and specifically defined.
[0031] The terms used in this specification are for describing the embodiments and are not intended to limit the present invention. In this specification, the singular form includes the plural form unless otherwise specified in the phrase. The words "including" and "having" used in the specification do not exclude the presence or addition of one or more other components other than the components mentioned.
[0032] In this specification, when a part includes a certain component, this does not mean that it excludes other components, but that it may further include other components, unless specifically stated to the contrary.
[0033] In this specification, the statement "A and / or B" means A or B, or A and B.
[0034] In this specification, "%" means % by weight, unless expressly indicated otherwise.
[0035] In this specification, D 50 D means the particle size that corresponds to 50% of the cumulative volume in the particle size distribution curve. 50 can be measured, for example, by using a laser diffraction method. The laser diffraction method generally makes it possible to measure particle sizes from the submicron range to about several mm, and can obtain results with high reproducibility and high resolution.
[0036] In the present specification, the term "multi-stage rolling" refers to rolling performed multiple times as opposed to single rolling, and the term "initial rolling" refers to the first rolling performed on a positive electrode active material layer prepared by drying a positive electrode slurry composition.
[0037] In this specification, the thickness change rate (%) can be calculated according to the following formula 1.
[0038] [Formula 1] Thickness change rate (%) = {thickness of the positive electrode active material layer rolled (K-1) times - thickness of the positive electrode active material layer rolled K times} x 100 / thickness of the positive electrode active material layer before rolling
[0039] In the above formula 1, K is an integer of 1 or more and N or less, and N is an integer of 2 or more.
[0040] In this specification, the rolling ratio (%) can be calculated according to the following formula 2.
[0041] [Formula 2] Rolling ratio (%) = {(thickness of the positive electrode active material layer before the rolling stage - thickness of the positive electrode active material layer after K rolling stages) / thickness of the positive electrode active material layer before the rolling stage} x 100
[0042] In this specification, the porosity can be calculated according to the following Equation 3.
[0043] [Formula 3] Porosity = {1-(density of the positive electrode active material layer after K rollings / density of the ideal positive electrode active material layer)} x 100
[0044] Here, the "ideal density of the positive electrode active material layer" refers to the density of a hypothetical positive electrode active material layer in which the positive electrode active material, conductive material, binder, etc. are filled without voids in a positive electrode containing 95% to 100% lithium iron phosphate as the positive electrode active material, and in the embodiment of the present invention, it was 3.39 g / cc. The porosity may vary depending on the mixture ratio of the positive electrode active material, conductive material, binder, etc., but is known to have a value within the range of 3.3 g / cc to 3.5 g / cc.
[0045] In this specification, "after the rolling step" means after all of the rolling steps, which are made up of a plurality of steps, are completed.
[0046] The present invention will now be described in further detail.
[0047] <Method of manufacturing positive electrode for lithium secondary battery> The method for producing a positive electrode for a lithium secondary battery of the present invention includes: (S1) a step of applying a positive electrode slurry composition containing lithium iron phosphate and a binder onto a current collector, and drying the composition to form a positive electrode active material layer; and (S2) a rolling step of performing a rolling process on the positive electrode active material layer N times (N is an integer of 2 or more).
[0048] In this case, during the first rolling, the thickness change rate of the positive electrode active material layer according to the following formula 1 is in the range of 5% to 15%, and during rolling after the first rolling, the thickness change rate of the positive electrode active material layer according to the following formula 1 is 3.5% or less.
[0049] [Formula 1] Thickness change rate (%) = {thickness of the positive electrode active material layer rolled (K-1) times - thickness of the positive electrode active material layer rolled K times} x 100 / thickness of the positive electrode active material layer before rolling
[0050] In the above formula 1, K is an integer of 1 or more and N or less.
[0051] Since lithium iron phosphate has a non-spherical shape, the density of the tap is low, and therefore a high rolling ratio is required during the rolling process of the positive electrode slurry in order to obtain a high-density positive electrode. However, when the positive electrode slurry is rolled at a high rolling ratio, there is a problem in that the positive electrode active material layer is detached due to the difference in mechanical properties between the positive electrode current collector and the positive electrode active material layer.
[0052] In order to solve such problems, the inventors have conducted extensive research and found that when a positive electrode slurry containing lithium iron phosphate is rolled multiple times, the positive electrode active material layer can be prevented from detaching from the positive electrode current collector by rolling the positive electrode slurry multiple times so that the thickness change rate after the second rolling is 3.5% or less, and thus completed the present invention. When the positive electrode slurry is rolled multiple times so that the thickness change rate after the second rolling is 3.5% or less as in the present invention, a high-density positive electrode having excellent positive electrode adhesion can be manufactured even if the binder content in the positive electrode slurry composition is relatively reduced. This will be described in detail below.
[0053] (1) Applying and drying the positive electrode slurry composition The method for preparing a positive electrode for a lithium secondary battery according to the present invention may include a step of coating a positive electrode slurry composition on a positive electrode current collector and drying the composition.
[0054] The positive electrode slurry composition may be prepared by mixing or dispersing a positive electrode active material and a binder in a solvent. The positive electrode slurry composition may also be prepared by additionally mixing or dispersing a conductive material and a dispersant in addition to the positive electrode active material and the binder in a solvent, if necessary.
[0055] The positive electrode current collector is not particularly limited as long as it is conductive and does not induce chemical changes in the battery. For example, the current collector may be stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, or the like.
[0056] The positive electrode current collector may have a thickness of 3 μm to 500 μm, and may have fine irregularities on its surface to enhance adhesion to the positive electrode active material layer. For example, the positive electrode current collector may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0057] The positive electrode active material according to the present invention may include lithium iron phosphate. Since lithium iron phosphate has an olivine structure, the active material structure is stably maintained at high temperatures compared to lithium transition metal oxides having a layered structure. As a result, when lithium iron phosphate is used as a positive electrode active material, the high temperature stability and high temperature life characteristics of the positive electrode are significantly improved, thereby reducing the risk of fire of a lithium secondary battery including the positive electrode.
[0058] The lithium iron phosphate may be a compound represented by the following chemical formula 1.
[0059] [Chemical formula 1] Li 1+a Fe 1-x M x (PO 4-b )X b
[0060] In the above Chemical Formula 1, M includes any one or more elements selected from the group consisting of Al, Mg, Ni, Co, Mn, Ti, Ga, Cu, V, Nb, Zr, Ce, In, Zn, and Y, X includes any one or more elements selected from the group consisting of F, S, and N, and a, b, and x are -0.5≦a≦0.5, 0≦b≦0.1, and 0≦x≦0.5, respectively.
[0061] For example, the lithium iron phosphate can be LiFePO4 with an olivine crystal structure.
[0062] The lithium iron phosphate may have a monolithic structure consisting of primary particles. In the present invention, the term "monolithic structure" refers to a morphology phase in which particles are not aggregated and exist as independent phases. In contrast to the monolithic structure, a particle structure may be one in which small particles ("primary particles") are physically and / or chemically aggregated to form relatively large particles ("secondary particles").
[0063] When the lithium iron phosphate has a monolithic structure made of primary particles, the possibility of the lithium iron phosphate particles cracking during the rolling process is low compared to when it is made of secondary particles, which is preferable because the capacity loss due to the detachment of the cracked particles is small. Also, when the lithium iron phosphate is made of monolithic primary particles, the migration of the binder during the drying process of the positive electrode slurry can be mitigated, which may be preferable in terms of the interfacial adhesion between the positive electrode current collector and the positive electrode active material layer.
[0064] The lithium iron phosphate may include a carbon coating layer on the surface. When a carbon coating layer is formed on the surface of the lithium iron phosphate, the electrical conductivity is improved, and the resistance characteristics of the positive electrode may be improved.
[0065] The carbon coating layer may be formed using at least one raw material selected from the group consisting of glucose, sucrose, lactose, starch, oligosaccharides, polyoligosaccharides, fructose, cellulose, furfuryl alcohol polymers, ethylene and ethylene oxide block copolymers, vinyl resins, cellulose resins, phenol resins, pitch resins, and tar resins. Specifically, the carbon coating layer may be formed by mixing the raw material with the lithium iron phosphate and then heat treating the mixture.
[0066] Average particle size of lithium iron phosphate D 50 The average particle diameter D of the positive electrode active material may be 0.5 μm to 20.0 μm, preferably 0.5 μm to 10.0 μm, more preferably 0.6 μm to 3 μm, and further preferably 0.6 μm to 2.5 μm. 50 When satisfies the above range, the mobility of lithium in the lithium iron phosphate is improved, and the charge / discharge characteristics of the battery can be improved.
[0067] The BET specific surface area of lithium iron phosphate is 5m 2 / g~20m 2 / g, specifically 7m 2 / g~18m 2 / g, more specifically 9m 2 / g~16m 2 / g. This range corresponds to a lower value compared to typical lithium iron phosphate. When this range is satisfied, aggregation of the lithium iron phosphate can be effectively suppressed even in a positive electrode slurry composition having a relatively low content of a dispersant.
[0068] The lithium iron phosphate may be contained in the solid content of the positive electrode slurry composition at 94.90% by weight to 97.96% by weight, specifically 95.40% by weight to 97.68% by weight, more specifically 95.96% by weight to 97.55% by weight. When the content of the lithium iron phosphate satisfies the above range, sufficient positive electrode energy density can be ensured, thereby improving the battery capacity of the positive electrode.
[0069] The binder plays a role in binding the positive electrode active material and the conductive material, etc., and in aiding in binding to the current collector. Specific examples include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene butadiene rubber, fluororubber, and various copolymers thereof, and one or more of these may be used alone or in combination.
[0070] In the process of preparing the positive electrode slurry, a mixture including the positive electrode active material, binder, conductive material, dispersant, and solvent is stirred, and a shear force is applied to the positive electrode slurry in the stirring process. At this time, the carbon coating layer formed on the surface of the lithium iron phosphate is bonded to the functional group of the binder, so that gelation of the positive electrode slurry composition may occur in the process of preparing the positive electrode slurry. The gelation may be more severe as the size of the lithium iron phosphate particles becomes smaller.
[0071] In order to prevent such gelation of the positive electrode slurry, it is preferable that the polyvinylidene fluoride satisfies the following formula 4.
[0072] [Formula 4] 0≦{(2A+B) / (C+D)}×100<0.2
[0073] The above A, B, C and D are the same as those of the above polyvinylidene fluoride. 1 This is the integrated area of each peak that appears at 11.5 ppm to 12.8 ppm, 3.9 ppm to 4.2 ppm, 2.6 ppm to 3.2 ppm, and 2.1 ppm to 2.35 ppm during H-NMR measurement.
[0074] In this case, the range from 11.5 ppm to 12.8 ppm is the range of the COOH functional group contained in polyvinylidene fluoride (PVDF). 1The H-NMR peak region is from 3.9 ppm to 4.2 ppm, which corresponds to the OCH2 functional group in polyvinylidene fluoride (PVDF). 1 The 2.6 ppm to 3.2 ppm range is the peak region of polyvinylidene fluoride (PVDF) monomers bonded head-to-head. 1 The H-NMR peak region is from 2.1 ppm to 2.35 ppm, which is the region of polyvinylidene fluoride (PVDF) monomers bonded head-to-tail. 1 The peak areas in the H-NMR spectra are shown.
[0075] On the other hand, polyvinylidene fluoride (PVDF) satisfying the above formula 4 means that the content of polar functional groups such as COOH and OCH2 in polyvinylidene fluoride is relatively small.
[0076] If the polyvinylidene fluoride contained in the binder in the positive electrode slurry does not satisfy Formula 1, a large number of hydrogen bonds may be formed between the functional groups (e.g., COOH, OCH2) in the binder and the hydrogen on the carbon coating layer, which may cause gelation of the positive electrode slurry composition.
[0077] On the other hand, when the polyvinylidene fluoride contained in the binder in the positive electrode slurry satisfies the above formula 4, the binder contains fewer functional groups, thereby reducing the number of hydrogen bonds between the functional groups and hydrogen on the carbon coating layer, thereby preventing gelation of the positive electrode slurry, improving the coating processability of the positive electrode slurry, and allowing the thickness and / or surface of the coated positive electrode active material layer to be uniform.
[0078] In particular, the effect of preventing gelation of the positive electrode slurry may be more pronounced when lithium iron phosphate is used as the positive electrode active material. Specifically, lithium iron phosphate has a smaller average particle size and a larger specific surface area than conventional positive electrode active materials such as lithium nickel cobalt manganese oxide, which increases the number of sites where the hydrogen bonds can occur, making the gelation more likely to occur. For this reason, polyvinylidene fluoride contained in the binder in the positive electrode slurry satisfies formula 4, thereby significantly reducing the possibility of gelation occurring in the positive electrode slurry using lithium iron phosphate as the positive electrode active material.
[0079] In addition, the polyvinylidene fluoride-based polymer binder has a stronger tendency to bond with lithium iron phosphate than with the positive electrode current collector. However, polyvinylidene fluoride satisfying the above formula 1 has a weaker bonding strength with lithium iron phosphate than polyvinylidene fluoride not satisfying the above formula 4, and as a result, the interfacial adhesion strength between the positive electrode active material layer and the current collector can be improved.
[0080] Preferably, the binder may be a homopolymer of polyvinylidene fluoride (PVDF). For example, when the binder is a homopolymer of polyvinylidene fluoride, the binder does not have a polar functional group, so that hydrogen bonds are not formed between the carbon coating layer and the binder, thereby preventing gelation of the positive electrode slurry composition.
[0081] The weight average molecular weight of the binder may be 20,000 g / mol to 1,200,000 g / mol, specifically 100,000 g / mol to 1,000,000 g / mol, more specifically 400,000 g / mol to 980,000 g / mol. When the weight average molecular weight of the binder satisfies the above range, the positive electrode slurry composition may have a viscosity suitable for a coating process, which is preferable in that the uniformity of the positive electrode active material layer formed from the composition is ensured and the positive electrode adhesive strength is improved.
[0082] According to one embodiment of the present invention, the binder may be included in the solid content of the positive electrode slurry composition in an amount of 0.5 wt % to 3.5 wt %, specifically 0.5 wt % to 3.0 wt %, and more specifically 0.5 wt % to 1.5 wt %.
[0083] According to the present invention, when a positive electrode slurry containing lithium iron phosphate is rolled multiple times, the second rolling step is performed so that the thickness change rate is 3.5% or less, thereby producing a high density positive electrode having excellent positive electrode adhesion even if the binder content in the positive electrode slurry composition is at a low level. In addition, the low binder content in the positive electrode active material layer can reduce the resistance of the lithium secondary battery, and the positive electrode active material content in the positive electrode active material layer can be relatively increased, thereby improving the battery capacity of the positive electrode.
[0084] The conductive material is not particularly limited as long as it has conductivity without inducing chemical changes in the battery, and examples thereof include graphite; carbon black such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and summer black; conductive fibers such as carbon fibers and metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives. Among these, carbon nanotubes, carbon nanofibers, and carbon black are preferred as the conductive material of the present invention, and carbon nanotubes are most preferred. The conductive network of carbon nanotubes can alleviate the phenomenon of the binder floating up during the drying process of the positive electrode slurry, and is therefore most preferred as the conductive material contained in the positive electrode of the present invention.
[0085] Carbon nanotubes are graphite sheets with a cylindrical shape and a nano-sized diameter. 2Carbon nanotubes have a bond structure and exhibit conductive or semiconductive properties depending on the angle and structure of the graphite sheet rolling. Carbon nanotubes can be classified into single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes depending on the number of bonds forming the wall, and these carbon nanotubes can be suitably selected depending on the application of the dispersion.
[0086] In addition, the carbon nanotube may have a secondary shape formed by agglomeration or arrangement of a plurality of carbon nanotubes, for example, a bundle- or rope-shaped carbon nanotube in which a plurality of carbon nanotubes are aligned or arranged in a certain direction, or an entangled-type carbon nanotube in which a plurality of carbon nanotubes are entangled in a ball or potato shape without a certain direction. In terms of dispersibility, the carbon nanotube is more preferably a bundle-type carbon nanotube.
[0087] The BET specific surface area of the carbon nanotubes is 100m 2 / g~1000m 2 / g, 150m 2 / g~800m 2 / g, 150m 2 / g~500m 2 / g, 150m 2 / g~300m 2 / g, or 150m 2 / g~200m 2 / g.
[0088] When the conductive material is carbon nanotubes, the conductive material may be contained in the solid content of the positive electrode slurry composition at 1.5 wt% or less, specifically 0.5 wt% to 1.0 wt%, more specifically 0.6 wt% to 1.0 wt%. When the content of the conductive material in the solid content of the positive electrode slurry composition satisfies the above range, the positive electrode conductive network is ensured, thereby improving the electrical conductivity of the positive electrode.
[0089] The dispersant prevents the lithium iron phosphate from being excessively aggregated in the positive electrode slurry composition, and allows the lithium iron phosphate to be effectively dispersed and present in the prepared positive electrode active material layer.
[0090] The dispersant may include a hydrogenated nitrile copolymer, specifically, the dispersant may be a hydrogenated nitrile copolymer.
[0091] Specifically, the hydrogenated nitrile copolymer may be a copolymer containing a structural unit derived from an α,β-unsaturated nitrile and a structural unit derived from a hydrogenated conjugated diene, or a copolymer containing a structural unit derived from an α,β-unsaturated nitrile, a structural unit derived from a conjugated diene, and a structural unit derived from a hydrogenated conjugated diene. As the α,β-unsaturated nitrile monomer, for example, acrylonitrile or methacrylonitrile may be used, and one or a mixture of two or more of these may be used. As the conjugated diene monomer, for example, a conjugated diene monomer having 4 to 6 carbon atoms such as 1,3-butadiene, isoprene, or 2,3-methylbutadiene may be used, and one or a mixture of two or more of these may be used.
[0092] More specifically, the hydrogenated nitrile copolymer may be hydrogenated nitrile butadiene rubber (H-NBR).
[0093] The weight average molecular weight of the dispersant may be 10,000 g / mol to 150,000 g / mol, preferably 15,000 g / mol to 140,000 g / mol, and more preferably 20,000 g / mol to 130,000 g / mol, which is smaller than the weight average molecular weight of the dispersant contained in the conventional positive electrode slurry composition.
[0094] If the weight average molecular weight of the dispersant is less than 10,000 g / mol, the dispersibility of the lithium iron phosphate is reduced, and the dispersant is eluted during the preparation of the electrode.If the weight average molecular weight of the dispersant is more than 150,000 g / mol, the positive electrode slurry composition has a high viscosity, which may reduce the stability and coating processability of the positive electrode slurry composition, and the conductive material is aggregated in a linear shape, which is undesirable in terms of the resistance of the lithium secondary battery.
[0095] The dispersant may be contained in the solid content of the positive electrode slurry composition in an amount of 1.5 wt % or less, specifically 1.2 wt % or less, more specifically 0.1 wt % to 1.0 wt %. When the content of the dispersant satisfies the above range, the aggregation of the conductive material in the solid content of the positive electrode slurry composition may be suppressed, thereby improving the positive electrode conductive network.
[0096] Meanwhile, in the method for manufacturing a positive electrode according to the present invention, the process of applying the positive electrode slurry composition to a positive electrode current collector may be performed by a method commonly known in the art, for example, by uniformly dispersing the composition using a doctor blade, or by a method such as die casting, comma coating, screen printing, etc.
[0097] Meanwhile, in the method for producing a positive electrode according to the present invention, a drying process of the positive electrode slurry composition applied on the positive electrode current collector may be performed by a commonly known method, for example, a heat treatment method such as a vacuum heat treatment in a certain temperature range or hot air injection.
[0098] At this time, the temperature range of the drying process may be 60° C. to 130° C., specifically 80° C. to 130° C., more specifically 100° C. to 130° C. At this time, when the temperature satisfies the above range, the moisture content in the lithium iron phosphate can be minimized, and volatile components contained in the process can be sufficiently removed, thereby preventing side reactions caused by these components and deterioration of battery characteristics during subsequent charging and discharging of the battery.
[0099] The time required for the drying step can be 5 minutes to 3 hours, specifically 5 minutes to 20 minutes, and more specifically 5 minutes to 10 minutes.
[0100] In the drying step, the positive electrode slurry composition applied onto the positive electrode current collector is dried, and a positive electrode active material layer is formed.
[0101] (2) Forming a positive electrode active material layer by performing N-stage rolling The method for manufacturing a positive electrode for a lithium secondary battery according to the present invention includes a rolling step of forming a positive electrode active material layer by performing multi-stage rolling N times (N is an integer of 2 or more) on the positive electrode active material layer prepared by drying the positive electrode slurry composition. In this case, the initial rolling step performed first may be a step of preliminarily rolling the dried positive electrode slurry composition so that a rolling step after the initial rolling step can be easily performed.
[0102] The first rolling step may be performed by a roll press method, but is not limited thereto. For example, the first rolling step may be performed by a hot press method.
[0103] Before the first rolling step is performed, the porosity of the dried positive electrode slurry composition may be 55% or less, specifically 35% to 55%, more specifically 40% to 55%. When the porosity of the dried positive electrode slurry composition satisfies the above range, it is preferable in that the rolling step of the dried positive electrode slurry composition is easy.
[0104] The first rolling step may be performed until the thickness change rate of the positive electrode active material layer exceeds a specific value. For example, the first rolling step may be performed such that the thickness change rate of the positive electrode active material layer according to the following formula 1 before / after the first rolling step is 5% to 15%, specifically 8% to 15%, more specifically 10% to 15%.
[0105] [Formula 1] Thickness change rate (%) = {thickness of the positive electrode active material layer rolled (K-1) times - thickness of the positive electrode active material layer rolled K times} x 100 / thickness of the positive electrode active material layer before rolling
[0106] In the above formula 1, K is an integer of 1 or more and N or less.
[0107] When the thickness change rate of the positive electrode active material layer during the first rolling process satisfies the above range, the positive electrode slurry composition may be sufficiently rolled to the extent that the positive electrode active material layer is not detached, thereby minimizing the number of rolling steps in the subsequent rolling process.
[0108] When the thickness change rate of the positive electrode active material layer falls within the above range and the first rolling process is completed, a subsequent rolling process may be performed successively.
[0109] In the method for producing a positive electrode for a lithium secondary battery according to the present invention, in a rolling step carried out after the first rolling step, rolling is performed so that the thickness change rate of the positive electrode active material layer according to the above formula 1 is 3.5% or less. At this time, the thickness change rate may be 0.1% to 3.5%, more specifically 0.5% to 3.5%.
[0110] The rolling steps after the first rolling step may be performed by a roll press method, but are not limited thereto. For example, the second rolling step may be performed by a hot press method.
[0111] If the thickness change rate of the positive electrode active material layer according to the above formula 1 exceeds 3.5% during the rolling process after the first rolling, a portion of the preliminary positive electrode active material layer having a weak strength (e.g., a portion having a thickness thinner than the average thickness or an edge portion) may crack, and the positive electrode active material layer may become detached from the positive electrode current collector.
[0112] The thickness change rate (%) described above corresponds to the rolling ratio change rate (%p). Here, the rolling ratio (%) can be calculated according to the following formula 2, and the rolling ratio change rate (%p) can be calculated according to the following formula 5.
[0113] [Formula 2] Rolling ratio (%) = {(thickness of the positive electrode active material layer before the rolling stage - thickness after K rolling stages) / thickness of the positive electrode active material layer before the rolling stage} x 100
[0114] [Formula 5] Change rate of rolling ratio (%p)={rolling ratio of the positive electrode active material layer rolled K times-rolling ratio of the positive electrode active material layer rolled (K-1) times}
[0115] Thereby, in the method for producing a positive electrode according to the present invention, in the rolling step after the first rolling, the rolling rate change rate can be 3.5%p or less, specifically 0.1%p to 3.5%p, and more specifically 0.5%p to 3.5%p.
[0116] In the rolling step, the total number of rolling operations may be 6 or less, specifically 3 to 6 times, and more specifically 4 to 6 times.
[0117] If the total number of rolling processes exceeds six, the thickness of the positive electrode active material layer becomes excessively thin, and as a result, a portion of the preliminary positive electrode active material layer that is weaker in strength (e.g., a portion having a thickness thinner than the average thickness or an edge portion) may crack, causing the positive electrode active material layer to detach from the current collector.
[0118] After the rolling step, the thickness of the positive electrode active material layer may be 85 μm to 95 μm, specifically 85 μm to 92 μm, more specifically 85 μm to 91 μm. When the thickness of the positive electrode active material layer after the rolling step satisfies the above range, a high-density positive electrode can be manufactured while preventing the positive electrode active material layer from being detached.
[0119] After the rolling step, the porosity of the positive electrode active material layer may be 28% to 36%, specifically 28.5% to 36%, more specifically 29% to 36%. Here, after the rolling step means after all of the rolling processes consisting of multiple times are completed, and the porosity may be calculated according to the following Equation 3.
[0120] [Formula 3] Porosity = {1-(density of the positive electrode active material layer after K rollings / density of the ideal positive electrode active material layer)} x 100
[0121] Here, the "ideal density of the positive electrode active material layer" refers to the density of a hypothetical positive electrode active material layer in which the positive electrode active material, conductive material, binder, etc. are filled without voids in a positive electrode containing 95% to 100% lithium iron phosphate as the positive electrode active material. The void ratio may vary depending on the mixture ratio of the positive electrode active material, conductive material, binder, etc., but is known to have a value within the range of 3.3 g / cc to 3.5 g / cc.
[0122] The porosity of the positive electrode active material layer after the rolling step is related to the thickness of the positive electrode active material layer after the rolling step. Therefore, when the porosity of the positive electrode active material layer after the rolling step satisfies the above range, a high-density positive electrode can be manufactured while preventing detachment of the positive electrode active material layer.
[0123] After the rolling step, the rolling ratio of the positive electrode active material layer may be 20% to 26%, specifically 22% to 26%, more specifically 23% to 26%. When the rolling ratio of the positive electrode active material layer after the rolling step satisfies the above range, a high-density positive electrode can be manufactured while preventing detachment of the positive electrode active material layer.
[0124] The present invention will be described in more detail below with reference to examples. However, the following examples are merely for the purpose of illustrating the present invention, and the scope of the present invention is not limited to these examples alone.
[0125] <Example 1: Production of positive electrode> (1) Preparation of Positive Electrode Slurry Composition Average particle size D 50A LiFePO4 positive electrode active material having a particle size of 2.4 μm, a carbon nanotube (CNT) conductive material, a polyvinylidene fluoride (PVDF) binder, and a hydrogenated nitrile butadiene rubber (H-NBR) dispersant were added to an N-methylpyrrolidone (NMP) solvent and stirred to prepare a positive electrode slurry composition. In the positive electrode slurry composition, the positive electrode active material, the conductive material, the binder, and the dispersant were present in a weight ratio of 97.4:0.8:1.0:0.8, and the solid content of the positive electrode slurry composition was 63 wt%.
[0126] (2) Manufacturing of positive electrodes The final fabricated positive electrode on a 20 μm thick aluminum thin film current collector had a discharge specific capacity of 156.7 mAh / cm 2 After the positive electrode slurry composition was applied so as to obtain a positive electrode slurry having a thickness of 100 μm, the positive electrode slurry composition was vacuum dried at 130° C. for 10 hours.
[0127] Thereafter, the dried positive electrode active material layer having an initial thickness of 115 μm was subjected to a rolling step. Specifically, the dried positive electrode active material layer was rolled by a roll press method, and the rolling step was performed a total of six times.
[0128] In the first rolling, the positive electrode active material layer was rolled so that the thickness change rate was 10.4%, and in the subsequent rolling, the positive electrode active material layer was rolled so that the thickness change rate was 3.5%, 2.6%, 1.8%, 1.7%, and 3.5%, respectively, to produce a positive electrode.
[0129] At this time, after each rolling step, the porosity of the positive electrode active material layer was calculated by substituting 3.39 g / cc into the "ideal density of the positive electrode active material layer" in the following formula 3. The results are shown in Table 1.
[0130] [Formula 3] Porosity = {1-(density of the positive electrode active material layer after K rollings / density of the ideal positive electrode active material layer)} x 100
[0131] <Comparative Example 1: Production of Positive Electrode> A positive electrode was manufactured in the same manner as in Example 1, except that the rolling step was performed once in total, and the rolling was performed so that the thickness change rate of the positive electrode active material layer was 22.6%.
[0132] <Comparative Example 2: Production of Positive Electrode> In the rolling step, a total of four rolling processes were performed. The positive electrodes were manufactured in the same manner as in Example 1, except that the rolling processes after the first rolling were performed so that the thickness change rates of the positive electrode active material layer were 3.5%, 5.2%, and 3.5%, respectively.
[0133] <Comparative Example 3: Production of Positive Electrode> A total of seven rolling steps were performed on the positive electrode active material layer having an initial thickness of 122 μm. The positive electrode was manufactured in the same manner as in Example 1, except that the positive electrode active material layer was rolled so that the thickness change rate of the positive electrode active material layer was 13.9% during the first rolling step, and the thickness change rates of the positive electrode active material layer were 3.3%, 2.5%, 1.6%, 2.5%, 0.8%, and 1.6% during the rolling steps after the first rolling step, respectively.
[0134] <Comparative Example 4> In the rolling step, the positive electrode was produced by rolling twice in total. In the first rolling, the positive electrode active material layer was rolled to have a thickness change rate of 10.4%, and in the subsequent rolling, the positive electrode active material layer was rolled to have a thickness change rate of 12.1%.
[0135] [Table 1]
[0136] <Experimental example - Checking for detachment of the positive electrode active material layer with the naked eye> The positive electrodes produced in Example 1 and Comparative Examples 1 to 4 were each observed with the naked eye to check for the presence or absence of detachment of the positive electrode active material layer.
[0137] Specifically, the positive electrodes produced in Example 1 and Comparative Examples 1 to 4 were visually observed to determine whether the rolled positive electrode active material layer had detached from the positive electrode current collector. The results are shown in Table 2 below.
[0138] ○: Detachment of the positive electrode active material layer occurs ×: Detachment of the positive electrode active material layer does not occur.
[0139] The positive electrodes prepared in Example 1 and Comparative Examples 1 to 3 are shown in Fig. 1 to Fig. 4. Specifically, Fig. 1 is a photograph of the positive electrode prepared in Example 1, Fig. 2 is a photograph of the positive electrode prepared in Comparative Example 1, Fig. 3 is a photograph of the positive electrode prepared in Comparative Example 2, and Fig. 4 is a photograph of the positive electrode prepared in Comparative Example 3.
[0140] [Table 2]
[0141] From the above Table 2 and Figs. 1 and 2, it can be confirmed that the positive electrode of Comparative Example 1, which was subjected to only one rolling, differs from the positive electrode of Example 1 in that detachment of the positive electrode active material layer occurs.
[0142] Furthermore, from Table 2, FIGS. 1 and 3, it can be seen that the positive electrodes of Comparative Example 2 and Comparative Example 4, which were rolled so that the thickness change rate exceeded 3.5% during rolling after the first rolling, experienced detachment of the positive electrode active material layer, unlike the positive electrode of Example 1.
[0143] Furthermore, from Table 2, Figs. 1 and 4, it can be seen that the positive electrode of Comparative Example 3, which was rolled more than five times even when rolled to a thickness change rate of 3.5% or less after the first rolling, experienced detachment of the positive electrode active material layer, unlike the positive electrode of Example 1.
Claims
1. (S1) applying a positive electrode slurry composition containing lithium iron phosphate and a binder onto a current collector and drying the composition to form a positive electrode active material layer; and (S2) a rolling step of rolling the positive electrode active material layer N times (N is an integer of 2 or more), In the rolling step, During the first rolling, the thickness change rate of the positive electrode active material layer according to the following formula 1 is 5% to 15%, During rolling after the first rolling, the thickness change rate of the positive electrode active material layer according to the following formula 1 is 3.5% or less, [Formula 1] Thickness change rate (%)={thickness of the positive electrode active material layer rolled (K−1) times−thickness of the positive electrode active material layer rolled K times}×100 / thickness of the positive electrode active material layer before rolling In the formula 1, K is an integer of 1 or more and N or less, The method for manufacturing a positive electrode for a lithium secondary battery, wherein the rolling ratio of the positive electrode active material layer after the rolling step is 20% to 26%.
2. 2. The method of claim 1, wherein the rolling step is performed in a multi-stage rolling process three to six times.
3. 3. The method for manufacturing a positive electrode for a lithium secondary battery according to claim 1, wherein the porosity of the positive electrode active material layer after the rolling step is 28% to 36%.
4. 3. The method of claim 1, wherein the thickness of the positive electrode active material layer after the rolling step is 85 μm to 95 μm.
5. 3. The method for producing a positive electrode for a lithium secondary battery according to claim 1, wherein the porosity of the dried positive electrode slurry composition is 55% or less.
6. 3. The method for producing a positive electrode for a lithium secondary battery according to claim 1, wherein the rolling ratio of the positive electrode active material layer after the first rolling is 10% or more.
7. The method of claim 1 or 2, wherein the rolling step is performed by a roll press method.
8. The lithium iron phosphate is a compound represented by the following formula 1: [Chemical formula 1] Li 1+a Fe 1-x M x (PO 4-b )X b 3. The method for producing a positive electrode for a lithium secondary battery according to claim 1, wherein, in Chemical Formula 1, M is any one or more elements selected from the group consisting of Al, Mg, Ni, Co, Mn, Ti, Ga, Cu, V, Nb, Zr, Ce, In, Zn, and Y; X is any one or more elements selected from the group consisting of F, S, and N; and a, b, and x are -0.5≦a≦0.5, 0≦b≦0.1, and 0≦x≦0.5, respectively.
9. The lithium iron phosphate is LiFePO having an olivine crystal structure. 4 The method for producing a positive electrode for a lithium secondary battery according to claim 1 or 2,
10. 3. The method for producing a positive electrode for a lithium secondary battery according to claim 1, wherein the lithium iron phosphate is contained in an amount of 94.90% by weight to 97.96% by weight in the solid content of the positive electrode slurry composition.
11. 3. The method for producing a positive electrode for a lithium secondary battery according to claim 1, wherein the binder is contained in an amount of 0.5% by weight to 3.5% by weight in the solid content of the positive electrode slurry composition.
Citation Information
Patent Citations
Manufacture of sheet-like electrode plate and nonaqueous electrolyte battery
JP1998064521A
Lithium secondary battery and fabricating method for electrode plate
JP2000133316A